The athlete's clock how biology and time affect sport performance - Rowland, Thomas W.
In this exceptionally readable exploration of athletic achievement, Dr. Thomas Rowland draws practical conclusions from science and experience to describe how various aspects of time affect sport performance. Readers can investigate challenging questions such as whether athletes can be safely nurtured to greatness, and what the optimal time of day is for training. Dr. Rowland takes you to startling places to explore such questions. The winner if Australia's World Championship Cockroach race uses the same controllers that command how human run, bike, swim. The human drumming of the Chinese dragon boat mimics how our internal rhythms propel us forward. Go inside the mind of a competitive sprinter to discover what happens each step of the way in a 100-meter run. Accessible and fascinating, The Athlete's Clock: How Biology and Time Affect Sport Performance takes you on a wide-ranging journey into the complexity and beauty of the human body in motion. It will forever change the way you watch and participate in sports as you come to realize it's all in the timing.